The Adventures of Robin Hood - Williams, Marcia (Walker Books Ltd, 1996)
There's no greater hero in all literature than Robin Hood, the brave and just outlaw of Sherwood Forest. Told in lively comic-strip style, this book relates eleven action-packed and easy-to-read tales about Robin and his merry band.
Keywords: Other; Juvenile Fiction; Legends, Myths, Fables